Peer-to-peer energy trading potential: An assessment for the residential sector under different technology and tariff availabilities. (15th August 2020) - Neves, Diana; Scott, Ian; Silva, Carlos A.
Abstract: The increasing number of distributed renewable energy systems and smart-grid technologies, are transforming electricity grids and markets, allowing the growth of peer-to-peer (P2P) energy markets, where consumers and prosumers trade directly with each other. Policymakers are then faced with the task of assessing alternative ways to manage and organize the electricity grid and market. This work explores the potential of P2P energy trading under different available technologies and market paradigms, by analysing the economic benefits for residential consumers and prosumers, given different solar generation contexts and load flexibility levels. The model is applied to the Portuguese residential sector. Results show that with best techno-economic sizing solution for solar photovoltaic (PV), the greater economic gains come from flexibility, reaching a maximum of 28% for consumers and 55% for prosumers, in a P2P trading scenario. However, if we consider flexibility and a high-solar fraction PV sizing, the savings would reach 29% for consumers and 113% for prosumers. P2P economic benefits are found to depend on the type of participating agents involved, demand profile, PV surplus and monetization schemes, level of flexible equipment, which will greatly influence which trading strategies work best, meaning that each case study needs a tailored P2P trading scheme. Highlights: The potential economic benefits of different energy trading paradigms are analysed. Solar PV and load flexibility are considered as energy trading technologies. Typical consumers and prosumers from the Portuguese residential sector are assessed. P2P shows savings for consumers and prosumers up to 28% and 55%, respectively. If we consider flexibility, respective savings increase to 29% and 113%.